The Imperative in Classical Armenian from a Typological and Historical Perspective. - Avetyan, Sargis (Bulletin of Yerevan University B: Philology, 2021)
It is a common knowledge that the Imperative has a special form mainly for the second person singular in Classical Armenian, showing a variety of formations and sometimes doublets (especially, in the mediopassive inflection. cf. իմանամ, ացայ – իմա՛/իմա՛ց/իմացի՛ր, լուանամ, ացայ – լուա՛/լուացի՛ր, խօսիմ, եցայ – խօսեա՛/խօսեա՛ց). Based on a synchronic and diachronic analysis of the relevant evidence from Classical Armenian, an assumption is made that the same aorist stem (with the stem-final -cc having been dropped in polysyllabic -cc-aorist stems) was initially employed as a 2nd sing. imperative in both active and mediopassive inflection after the loss of post-tonic syllables in Pre-Written Armenian. Later, the polysyllabic -cc-aorist stem with the analogically restored final-cc as well as the root/-cc-aorist stem plus the ending -ir (ի՛ր) came to be used in the meaning of the 2nd sing. mediopassive imperative in order to differentiate between active and mediaopassive imperative forms, and partly due to system pressure and analogical extension. Therefore, the active forms of the 2nd sing. imperative of a number of middle/mediopassive verbs in Classical Armenian (cf. նստիմ, նստայ – նի՛ստ, դառնամ, դարձայ – դա՛րձ, լուանամ, ացայ – լուա՛ etc.), should be regarded as relict forms retained owing to the high frequency of use.